Factors contributing to rising imprisonment figures in Germany - Suhling, Stefan (The Howard journal of criminal justice, 2003)
The number of people incarcerated in German prisons has increased since the beginning of the 1990s. This article investigates possible reasons for the growth. By comparing two states (‘Länder’), it is shown that it is not so much the developments in crime that are essential. Rather, the data suggest that decision making by the prosecution and the courts plays an important role. Requirements for further research are outlined.